2016
DOI: 10.1186/s12888-016-0804-y
|View full text |Cite|
|
Sign up to set email alerts
|

Readmission rates of South Korean psychiatric inpatients by inpatient volumes per psychiatrist

Abstract: BackgroundReadmission rates of psychiatric inpatients are higher in South Korea than other Organization for Economic Co-operation and Development (OECD) countries. In addition, the solution for readmission control is deficient based on the characteristics of the South Korean National Health Insurance (NHI) system. Therefore, it is necessary to identify ways to reduce psychiatric inpatient readmissions. This study investigated the relationship between inpatient volume per psychiatrist and the readmission rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
2
13
1
1
Order By: Relevance
“…The 30-day readmission rate (16.69%) in this study was consistent with some studies conducted in other countries and settings [7,9]; nevertheless, the 30-day readmission rate had large variations from previous reports. A report published by the Organization for Economic Cooperation and Development suggested that the 30-day readmission rate for schizophrenia varied from 5 to 20% among 20 countries [39] and the 30-day readmission rate was 4.5% (1598/37,796) in a Korean sample [8]. The 1-year readmission rate (33.79%) in our study is similar to that reported in other studies [10,40] except the one reported by Zhou el al.…”
Section: Psychiatric Readmission Ratessupporting
confidence: 88%
See 1 more Smart Citation
“…The 30-day readmission rate (16.69%) in this study was consistent with some studies conducted in other countries and settings [7,9]; nevertheless, the 30-day readmission rate had large variations from previous reports. A report published by the Organization for Economic Cooperation and Development suggested that the 30-day readmission rate for schizophrenia varied from 5 to 20% among 20 countries [39] and the 30-day readmission rate was 4.5% (1598/37,796) in a Korean sample [8]. The 1-year readmission rate (33.79%) in our study is similar to that reported in other studies [10,40] except the one reported by Zhou el al.…”
Section: Psychiatric Readmission Ratessupporting
confidence: 88%
“…Moreover, repeated admissions could encourage dependency on inpatient services [7] and increase healthcare costs [5]. Therefore, readmission has long been recognized as a validated outcome measure for healthcare quality [8]. The commonly used timeframes to assess readmission were readmission within 30 days [3,5,7,9] and 1 year [2,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are only two studies on this issue in the field of psychiatric inpatient care. 6 , 7 A cross-sectional study of 673 patients in 25 hospitals across 11 countries found that lower patient-to-psychiatrist ratio (high staffing) was associated with higher treatment satisfaction (percentage of patients with low satisfaction: 18% in high-staffing hospitals and 40% in low-staffing hospitals). 6 Additionally, a cohort study of 35,884 patients in 53 hospitals in South Korea revealed that lower inpatient volume per psychiatrist (high staffing) – the total length of stay for mental disorders divided by the number of psychiatrists in a hospital – was associated with a lower 30-day readmission rate (odds for readmission in high-staffing vs low-staffing hospitals: 0.38).…”
Section: Introductionmentioning
confidence: 99%
“…Studien aus dem psychiatrischen und psychotherapeutischen Bereich weisen heterogene Ergebnisse auf [17,31]. So wurde im asiatischen Raum belegt, dass eine höhere Zahl stationär behandelter Patienten mit einer niedrigen Verweildauer assoziiert war, aber nicht mit der Reduzierung der Wiederaufnahmeraten [32,33]. Demgegenüber zeigte eine dänische Studie [34], dass große psychiatrische Krankenhäuser eine bessere Qualität der Behandlungsprozeduren aufwiesen als kleinere psychiatrische Krankenhäuser.…”
Section: Diskussionunclassified